Syndesmotic Screws, Is Routine Removal Necessary? A Systematic Review and Meta-Analysis - Daniel Acevedo BSc(Med); Andy Suarez BS; Kiranjit Kaur BS; Taylor Checkley BS; Pedro Jimenez BS; Aoife MacMahon MD; Ettore Vulcano MD; Amiethab A. Aiyer MD (Foot & Ankle Orthopaedics)
Category: Ankle; Trauma Introduction/Purpose: Syndesmotic injuries are commonly treated with syndesmotic screws, with subsequent screw removal routinely scheduled during the postoperative period. Recent studies have raised doubts about the necessity of routine removal, highlighting the lack of change in functional outcomes and the risks posed by a second surgery. Previous systematic reviews on this topic have not limited their inclusion criteria to Randomized Controlled Trials (RCTs), consequently lowering their level of evidence (LOE). Our study aimed to compare the functional outcomes and complication rates in patients undergoing routine syndesmotic screw removal versus those managed with an on-demand approach while providing a higher LOE than previous studies. Methods: In accordance with the guidelines on Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) we conducted a systematic search of seven databases (MEDLINE, Embase, Cochrane CENTRAL, CINAHL, Web of Science, PubMed, and ClinicalTrials.gov) for comparative studies on routine syndesmotic screw removal versus an on-demand approach to removal following acute ankle fractures or isolated syndesmotic injuries. Only prospective RCTs were considered for inclusion. Data reported by at least 2 studies were pooled for meta-analysis using Review Manager Software (RevMan 5.4.1). Mean differences were calculated for continuous outcomes while risk ratios were calculated for dichotomous outcomes; all measures were calculated with their respective 95% confidence intervals (CIs). Two-tailed tests of significance were performed with a value of 0.05. Heterogeneity was calculated using I2 index, Random-effect models were used for groups with high heterogeneity (I2 > 51%) while common-effect models were used for groups with low heterogeneity (I2 < 50%). Results: Of 630 potential articles, only 3 studies were ultimately chosen for inclusion. Pooled data analysis showed no significant difference in Olerud-Molander ankle scores (mean difference [MD] -2.36, 95% confidence interval [CI] -6.50 to 1.78, p = 0.26), American Orthopedic Foot and Ankle Hindfoot Score (MD -0.45, 95% CI -1.59 to .69, p = 0.44), or dorsiflexion (mean difference 2.20, 95% CI -0.50 to 4.89, p = 0.11) between the routine removal and on-demand removal groups at the one-year mark postoperatively. However, routine removal was associated with a significantly higher rate of overall complications compared to on-demand removal (risk ratio 3.02, 95% CI 1.64 to 5.54, p = 0.0004). Respectively, none of the included studies reported a significant difference in pain scores or range of motion. Conclusion: Our results did not show any significant difference in functional outcome scores between routine removal and on-demand removal of syndesmotic screws at 1-year postoperatively, suggesting that neither removal strategy significantly impacts functional recovery. However, the significantly higher incidence of complications in the routine removal group, raises important considerations regarding the potential disadvantages of this approach. Consequently, given the elevated risk of complications associated with routine removal and the lack of superior functional outcomes, we recommend adopting an as-needed approach to syndesmotic screw removal.